Metallopolymers in minutes via organocatalysis at room temperature. Issue 33 (2nd August 2022) - Oberle, Kjersti G.; Whitman, Elizabeth L.; Jolly, Charles S.; Webster, Katherine A.; Marx, Benjamin S.; Howard, Christopher M.; Hanger, Clara A.; Ramey, Erin E.; Zou, Yutong; Lowe, Jared C.; Turlington, Mark; Turlington, Christopher R.
Abstract : Organocatalytic ring-opening polymerization of cyclic carbonate monomers derivatized with metallocenes is described for the rapid synthesis of high M n metallopolymers. Abstract : The organocatalytic ring-opening polymerization (OROP) of cyclic carbonate monomers derivatized with metallocenes is described for the rapid synthesis of high M n metallopolymers where the metal is pendant to the polymer backbone. This work bridges the fields of organocatalysis and metallopolymers and establishes a new paradigm that metallic monomers can be compatible with OROP.